Experiences of transition processes from Grade 7 to Grade 8 in two South African schools: an exploratory study - Petra Engelbrect; Hannelie Louw; Julialet Rens (Perspectives in Education)
This paper focuses on exploring the transition South African learners make from Grade 7 to Grade 8, with an emphasis on the experiences of all the role players in two school cultures during this transition phase. This qualitative exploratory research project was placed in a constructivist research paradigm. The data were analysed in an exploratory and interpretative way by identifying segments that were responsive to our research questions. The participants in the two purposively selected South African schools included a voluntary sample of teachers, parents, and learners in Grade 8 using the draw-and-write technique and focus group interviews with each learner group based on the interpretation of their drawings. Focus group interviews were also conducted with a small group of the parents and teachers of the Grade 8 learners in the two schools, and individual interviews were conducted with the school principals. Findings indicate some common ground but also qualitative differences between the two schools with specific reference to the quality of educational opportunities and socio-emotional challenges that may influence social inequalities in future.